ARTIFICIAL INTELLIGENCE IN DENTISTRY AND MAXILLOFACIAL DIAGNOSTICS: CLINICAL APPLICATIONS OF AI-BASED RADIOLOGY AND ELASTOGRAPHY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In contemporary medical practice, artificial intelligence (AI) is transforming traditional diagnostic approaches, offering innovative solutions to enhance the accuracy and efficiency of clinical research. Dentistry and maxillofacial diagnostics represent promising areas for the application of machine learning and computer vision technologies.